2021
DOI: 10.3390/cancers13194844
|View full text |Cite
|
Sign up to set email alerts
|

Pancreatic Cancer Small Extracellular Vesicles (Exosomes): A Tale of Short- and Long-Distance Communication

Abstract: Even with all recent advances in cancer therapy, pancreatic cancer still has a dismal 5-year survival rate of less than 7%. The most prevalent tumor subtype is pancreatic ductal adenocarcinoma (PDAC). PDACs display an extensive crosstalk with their tumor microenvironment (TME), e.g., pancreatic stellate cells, but also immune cells to regulate tumor growth, immune evasion, and metastasis. In addition to crosstalk in the local TME, PDACs were shown to induce the formation of pre-metastatic niches in different o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 232 publications
(288 reference statements)
0
24
0
1
Order By: Relevance
“…It has also been suggested that autophagy in CAFs could be induced by ammonia produced by cancer cells during glutaminolysis and diffused into the microenvironment, which could lead to a positive feedback, with subsequent high levels of glutamine secreted into the TME by CAFs increasing the conversion of glutamine to glutamate and ammonia along with mitochondrial activity in cancer cells (166,167). A supportive role of the metabolic scavenging in PDAC is further evidenced by the confirmed existence of CAF-derived exosomes containing mRNA, miRNA, intact metabolites and TCA cycle intermediates, which promote PC cell proliferation, migration and chemoresistance in a mechanism similar to macropinocytosis under nutrient-depleted conditions (31,(168)(169)(170). Aside from acting as a direct source of metabolites, such exosomes could create a hypoxia-mimicking microenvironment stimulating the reductive carboxylation of glutamine in cancer cells, the pathway previously observed in rapidly growing malignant cells and identified to be an alternative to oxidative metabolism as the major source of citrate and precursors for macromolecular synthesis (168,171).…”
Section: Interactions Of Pancreatic Cancer Cells With the Stromal Env...mentioning
confidence: 98%
“…It has also been suggested that autophagy in CAFs could be induced by ammonia produced by cancer cells during glutaminolysis and diffused into the microenvironment, which could lead to a positive feedback, with subsequent high levels of glutamine secreted into the TME by CAFs increasing the conversion of glutamine to glutamate and ammonia along with mitochondrial activity in cancer cells (166,167). A supportive role of the metabolic scavenging in PDAC is further evidenced by the confirmed existence of CAF-derived exosomes containing mRNA, miRNA, intact metabolites and TCA cycle intermediates, which promote PC cell proliferation, migration and chemoresistance in a mechanism similar to macropinocytosis under nutrient-depleted conditions (31,(168)(169)(170). Aside from acting as a direct source of metabolites, such exosomes could create a hypoxia-mimicking microenvironment stimulating the reductive carboxylation of glutamine in cancer cells, the pathway previously observed in rapidly growing malignant cells and identified to be an alternative to oxidative metabolism as the major source of citrate and precursors for macromolecular synthesis (168,171).…”
Section: Interactions Of Pancreatic Cancer Cells With the Stromal Env...mentioning
confidence: 98%
“…The development of isolation kits to surmount this shortcoming will increase their accessibility. Immune purification to concentrate tumor-specific exosomes could increase sensitivity and specificity of the analysis 42 . The common ground across the eligible studies was, besides analysis of biomarkers associated with tumor development and aggressiveness, as previously mentioned, a low risk of bias regarding prognostic factor measurement -with clearly described methods for sampling and isolation of biomarkers.…”
Section: Implications For Research and Clinical Practicementioning
confidence: 99%
“…Exosomes are widely distributed in various body fluids [ 32 ] and contain adhesion molecules, tetrads, enzymes, scaffolds, nucleic acids, and binding proteins ( Figure 2 ) [ 33 ]. Nucleic acids, lipids, and proteins can be transferred between cells via exosomes [ 34 ], in some cases affecting recipient cells via autocrine and paracrine mechanisms [ 35 ]. There are multiple modes of action between target cells and exosomes.…”
Section: Exosome Classificationmentioning
confidence: 99%